Host-parasite interactions on an experimental landscape - Kosciuch, Karl L. (Kansas State University, 2006)
The reproductive strategies of avian brood parasites and the behavioral responses of their hosts have served as a model of co-evolution in nature. Host adaptations to reduce the costs of parasitism are countered with novel parasite behaviors that increase the success of the parasite and thereby decrease host productivity. Not all host species possess anti-parasite defense behaviors, and parasitism by Brown-headed Cowbirds (Molothrus ater) may cause population declines in some species. Bell’s Vireo (Vireo bellii) is a small-bodied cowbird host that fails to fledge young if successfully parasitized. Although vireos desert naturally parasitized nests, the cues that cause desertion have not been identified. Understanding how parasitism affects vireo productivity is important because cowbird removal is an integral component of the recovery efforts for the endangered Least Bell’s Vireo (V. b. pusillus) in California. However, it is generally unknown how cowbird removal affects vireo productivity. To address these issues, I monitored the productivity of vireos nesting in Kansas at the Konza Prairie Biological Station, conducted a clutch manipulation experiment, and experimentally removed cowbirds. In addition, I used stable isotope analysis to determine if recently fledged cowbird young could be assigned to habitats or host species. I found that vireos did not desert nests due to the presence of a cowbird egg; rather egg removal by cowbirds caused desertion, which is a generalized response in many taxa of birds. Cowbird removals decreased parasitism of vireo nests by approximately 36% and led to a 2-fold increase in vireo productivity per pair. Cowbird productivity from vireo pairs increased because fewer parasitized nests were deserted and parasitized nests on removal plots had a higher probability of success. No cowbird removal study has reported an increase in cowbird productivity in response to trapping. Cowbird nestlings from prairie plots and shrub plots differed in carbon and nitrogen isotope compositions, and 87% of locally produced juvenile cowbirds were classified with nestlings from shrub plots. Thus, the continued expansion of woody plants into tallgrass prairie may result in local increases in cowbird productivity.
Keywords: Brood parasitism; Brown-headed Cowbird; Bell's Vireo; Stable Isotope; Cowbird removal; productivity; Agriculture, Forestry and Wildlife (0478); Biology, Ecology (0329); Biology, Zoology (0472)